Study of Deep Sounding Time-Domain Electromagnetic (TDEM) Method Using Horizontal Electric Dipole to Infer Subsurface Resistivity Structure - Wahyu Srigutomo; Tsuneomi Kagiyama; Wataru Kanda; Hisashi Utada (Institut Teknologi Bandung, 2005)
Electromagnetic methods to infer subsurface resistivity structure particularly in volcanic and hydrothermal regions are considered highly effective to apply. Time domain electromagnetic (TDEM) method as one of them, is a robust method utilizing controlled-galvanic source which has higher ability to penetrate deeper structure. This paper tries to elaborate the theoretical formulation of TDEM with a long-grounded current wire for a layered-earth problem, the mathematical inversion algorithm to find the suitable model for interpretation as well as its sensitivity analysis, and the application to synthetic and real measured data.